2019
DOI: 10.1177/0269215519879212
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of manual therapy in patients with hemophilia and ankle arthropathy: a randomized clinical trial

Abstract: Objective: The aim of this study was to evaluate the effects of a manual therapy using fascial therapy on joint bleeding, joint pain and joint function in patients with hemophilic ankle arthropathy. Setting: Hemophilia patient associations. Design: Randomized, controlled trial, multicenter and intention-to-treat analysis. Participants: A total of 65 patients with hemophilic ankle arthropathy. Intervention: The experimental group ( n = 33) received one fascial therapy session per week for three weeks. The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
4
20
0
2
Order By: Relevance
“…In our study, we observed improvement in knee joint condition in patients with haemophilia who received manual therapy, especially in pain, range of motion and crepitus. Such improvements after the administration of traction and joint gliding techniques have already been reported by studies applying other manual therapy techniques 21,27 …”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In our study, we observed improvement in knee joint condition in patients with haemophilia who received manual therapy, especially in pain, range of motion and crepitus. Such improvements after the administration of traction and joint gliding techniques have already been reported by studies applying other manual therapy techniques 21,27 …”
Section: Discussionsupporting
confidence: 63%
“…The Hemophilia Joint Health Score was developed to assess joint health in people with haemophilia by evaluating joint structure and function. The age range of the patients included in our study was 23‐44 (IQR: 9.00), being similar to that of other studies using this scoring system to measure joint health in patients with haemophilic arthropathy 21,27 . This measuring instrument is used as a study variable in clinical trials and is considered optimal for assessing arthropathy in children and young adults.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations